Urine testing to monitor the impact of HPV vaccination in Bhutan and Rwanda. Issue 3 (15th April 2016) - Franceschi, Silvia; Chantal Umulisa, M.; Tshomo, Ugyen; Gheit, Tarik; Baussano, Iacopo; Tenet, Vanessa; Tshokey, Tshokey; Gatera, Maurice; Ngabo, Fidele; Van Damme, Pierre; Snijders, Peter J.F.; Tommasino, Massimo; et al.
Abstract : Bhutan (2010) and Rwanda (2011) were the first countries in Asia and Africa to introduce national, primarily school‐based, human papillomavirus (HPV) vaccination programmes. These target 12 year‐old girls and initially included catch‐up campaigns (13–18 year‐olds in Bhutan and ninth school grade in Rwanda). In 2013, to obtain the earliest indicators of vaccine effectiveness, we performed two school‐based HPV urine surveys; 973 female students (median age: 19 years, 5th‐95th percentile: 18–22) were recruited in Bhutan and 912 (19 years, 17–20) in Rwanda. Participants self‐collected a first‐void urine sample using a validated protocol. HPV prevalence was obtained using two PCR assays that differ in sensitivity and type spectrum, namely GP5+/GP6+ and E7‐MPG. 92% students in Bhutan and 43% in Rwanda reported to have been vaccinated (median vaccination age = 16, 5th–95th: 14–18). HPV positivity in urine was significantly associated with sexual activity measures. In Rwanda, HPV6/11/16/18 prevalence was lower in vaccinated than in unvaccinated students (prevalence ratio, PR = 0.12, 95% confidence interval, CI: 0.03–0.51 by GP5+/GP6+, and 0.45, CI: 0.23–0.90 by E7‐MPG). For E7‐MPG, cross‐protection against 10 high‐risk types phylogenetically related to HPV16 or 18 was of borderline significance (PR = 0.68; 95% CI: 0.45–1.01). In Bhutan, HPV6/11/16/18 prevalence by GP5+/GP6+ was lower in vaccinated than in unvaccinated students but CIs were broad. In conclusion, our study supports the feasibility of urine surveys to monitor HPV vaccination and quantifies the effectiveness of the quadrivalent vaccine in women vaccinated after pre‐adolescence. Future similar surveys should detect increases in vaccine effectiveness if vaccination of 12 year‐olds continues. Abstract : What's New? The self‐collection of urine for human papillomavirus (HPV) testing is a potential alternative to cervical sampling for the monitoring of HPV prevalence and HPV vaccination effectiveness in women. The present study indicates that urine surveys could be especially useful in Bhutan and Rwanda, which were among the first countries in Asia and Africa to implement school‐based HPV vaccination programmes. First‐void urine samples yielded evidence for lower prevalence of HPV types 6, 11, 16, and 18 in vaccinated versus unvaccinated female students ages 18 to 20. Women in this age group often are reluctant to undergo examination for cervical cytology.